Preparation method of recycled glass fiber reinforced epoxy-based wood-plastic flame-retardant board
Patent Information
- Application Number
- CN202610986904.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术的不足,本申请提供了回收玻纤增强环氧基木塑阻燃板材的制备方法,解决了现有废弃玻纤与木质纤维高填充环氧树脂体系黏度大难成型、界面化学结合弱以及固化收缩会致板材开裂的问题
1、本申请通过引入聚合二苯基甲烷二异氰酸酯与体系中的游离羟基在常温下发生加成反应,在环氧树脂基体中预先构建聚氨酯预聚合网络,该机制使出釜时的液态混合树脂糊在熟化阶段转变为表面无粘性的半固态可塑形态,克服常规工艺中高填充木质纤维和玻璃纤维导致的黏度难以控制的难题,使物料具备便于切块称重与加压充模的加工属性,改善多相混合体系在模具内的均质成型效果。
Smart Images

Figure CN122917355A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer composite materials technology, specifically a method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant boards. Background Technology
[0002] With the continuous development of the wind power industry, wind turbine blades that were in service in the early stages are gradually entering the retirement period, generating a large amount of waste glass fiber solid waste. Conventional landfill or simple downgrading treatment methods result in resource waste. Introducing it as a reinforcing filler into wood-plastic composites is a way to realize the recycling of solid waste resources. Epoxy resin, due to its good mechanical and adhesive properties, is often used as the continuous phase matrix for such composite boards.
[0003] In existing composite board manufacturing processes, there are still some technical drawbacks when waste glass fiber and wood fiber are mixed together with epoxy resin matrix. The addition of a large amount of fiber filler will cause the initial viscosity of the resin system to rise sharply, making it difficult for the material to be uniformly dispersed in the reactor. Moreover, microbubbles entrained during the mixing stage are extremely difficult to remove in the viscous system, which directly results in a high porosity inside the molded board. At the same time, due to the previous processing and long-term service, the recycled glass fiber from waste wind turbine blades lacks effective active groups on its surface, and the chemical bonding force between it and the organic resin matrix and wood fiber is weak. Conventional physical blending methods are difficult to eliminate the microscopic defects at the interface between the inorganic fiber and the organic matrix, and delamination will occur at the interface under stress.
[0004] Furthermore, epoxy resin undergoes volume shrinkage during high-temperature cross-linking and curing. Existing hot-press molding processes directly open the mold or allow conventional natural cooling after curing, without considering the compensating effect of the pressure on volume shrinkage and the relaxation and rearrangement requirements of polymer chain segments during cooling. The asynchronous shrinkage deformation caused by this cooling method will induce residual thermal stress inside the composite board, which will lead to internal microcracks or macroscopic warping deformation after demolding. This not only weakens the overall mechanical strength of the material, but also destroys the continuous flame-retardant carbonized layer structure, making it difficult for the molded board to meet stringent industrial application standards. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this application provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant boards, which solves the problems of high viscosity and difficulty in molding, weak interfacial chemical bonding, and cracking of boards caused by curing shrinkage in existing high-filled epoxy resin systems of waste glass fiber and wood fiber.
[0006] To achieve the above objectives, this application provides the following technical solution:
[0007] This application provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant boards, comprising the following steps: The viscosity of bisphenol A epoxy resin is reduced by heating, and polyvinyl butyral resin powder is added and sheared and stirred to form a homogeneous toughening resin liquid. Dicyandiamide, 2-methylimidazole and zinc stearate were added to the toughening resin solution in sequence and stirred evenly. The composite flame retardant filler was then sieved in and stirred to form a homogeneous resin paste. Wood fibers and surface-aminated modified waste wind turbine blade recycled glass fibers are added to the resin paste in batches and alternately, and then mixed to form a mixture. Polymerized diphenylmethane diisocyanate was injected into the mixture and stirred under vacuum, then discharged from the reactor; The mixture discharged from the reactor is placed in a closed environment to stand and mature until the material system presents a semi-solid plastic form. The matured premixed material is transferred into the mold cavity, the mold is closed, molding pressure is applied, and it is heated and hot-pressed to cure. Maintain molding pressure and perform step-by-step cooling. After cooling is complete, open the mold, eject the sheet, and allow it to cool and solidify naturally.
[0008] By adopting the above technical solution, the reaction mechanism and innovation of this application are reflected in the following stages: During the settling and maturation stage after the mixture is discharged from the reactor, the material is in a liquid paste state. At this time, the isocyanate groups at the end of the polymeric diphenylmethane diisocyanate molecule undergo a carbamate reaction with the free hydroxyl groups on the surface of the wood fiber and the free hydroxyl groups on the polyvinyl butyral resin molecule chain. This addition reaction proceeds spontaneously at room temperature. By consuming the free hydroxyl groups in the system, a polyurethane prepolymer network is constructed in the epoxy resin matrix. Macroscopically, the apparent viscosity of the system increases with time, and the material changes from the initial liquid paste state to a semi-solid plastic form with a basically non-sticky surface, giving the material properties similar to sheet molding compound, which can be weighed, cut into blocks, and molded.
[0009] Subsequently, during the heating and hot pressing process, the active amino layer attached to the surface of the recycled glass fiber of the waste wind turbine blade, which is modified by surface amination, has strong reactivity. Under heating conditions, the primary amine group conducts nucleophilic attack on the epoxy group at the end of the bisphenol A type epoxy resin molecule, resulting in a ring-opening addition reaction. This reaction process constructs a covalent bond connection between the inorganic glass fiber and the organic epoxy matrix, compensating for the microscopic defects at the interface between the two phases.
[0010] Meanwhile, dicyandiamide, which is insoluble in epoxy resin and relatively stable at room temperature, melts and dissociates when the molding temperature rises to the molding temperature. Under the catalytic reduction of activation energy by 2-methylimidazole, it rapidly initiates the addition polymerization of epoxy groups. The three-dimensional cross-linked network of epoxy resin and the prepolymerized polyurethane network generated in the early stage interpenetrate each other to form a semi-interpenetrating polymer network structure, which helps to improve the mechanical strength of the board body.
[0011] After hot pressing and curing, the epoxy matrix with high cross-linking density will shrink in volume. By performing step cooling while maintaining the molding pressure, the polymer chain segments can relax and rearrange during the cooling process, forcibly absorbing the deformation energy generated by cross-linking shrinkage, which greatly reduces the risk of residual thermal stress inside the board induced by asynchronous cooling shrinkage.
[0012] Preferably, the raw materials used to prepare the board contain the following components in parts by weight: 25 to 35 parts of bisphenol A type epoxy resin; 3 to 6 parts of polyvinyl butyral resin powder; 2 to 4 parts of dicyandiamide; 0.2 to 0.5 parts of 2-methylimidazole; 0.5 to 1 part of zinc stearate; 10 to 20 parts of composite flame retardant filler; 30 to 45 parts of wood fiber; 15 to 30 parts of recycled glass fiber from waste wind turbine blades with surface aminated modification; and 2 to 5 parts of polymeric diphenylmethane diisocyanate.
[0013] By adopting the above technical solution, a specific ratio of polymerized diphenylmethane diisocyanate, polyvinyl butyral resin, and wood fiber is set so that the molar amount of isocyanate groups is slightly lower than the total molar amount of free hydroxyl groups in the system. This is beneficial to promote the full consumption of isocyanate during the curing stage and minimize the problem of residual isocyanate causing side reactions and foaming during the subsequent high-temperature pressing stage.
[0014] Preferably, the surface-aminated recycled glass fiber from waste wind turbine blades is a waste glass fiber coarse material that retains the original fiber length, and its outer surface has an active amino layer generated by the hydrolysis and cross-linking of 3-aminopropyltriethoxysilane.
[0015] By adopting the above technical solution, the original fiber length is mainly maintained to preserve the macroscopic mechanical skeleton of the glass fiber. The silanol groups generated after the hydrolysis of 3-aminopropyltriethoxysilane can undergo condensation and dehydration reaction with the silanol groups on the exposed glass fiber surface after acid and alkali treatment to form Si-O-Si chemical bonds, thereby grafting free amino groups onto the inorganic fiber surface, which provides sufficient reaction sites for the subsequent high-temperature interfacial coupling stage.
[0016] Preferably, the composite flame-retardant filler is composed of aluminum hydroxide and montmorillonite; and the weight ratio of aluminum hydroxide to montmorillonite is 4:1.
[0017] By adopting the above technical solution, aluminum hydroxide undergoes an endothermic reaction and releases water of crystallization when it is heated and decomposes, thereby diluting the concentration of combustible gas at the combustion interface; the nano-sized montmorillonite sheets can form a continuous silicate carbonization barrier layer when the matrix is burned, and the synergistic effect of the two can slow down the transfer of oxygen and heat and improve the limiting oxygen index of the material.
[0018] Preferably, the step of adding wood fiber and surface-aminated waste wind turbine blade recycled glass fiber to the resin paste by batch alternating feeding method and mixing them to form a mixture includes: dividing the total amount of wood fiber and the total amount of surface-aminated waste wind turbine blade recycled glass fiber into multiple equal parts, first adding one part of wood fiber and stirring, then adding one part of surface-aminated waste wind turbine blade recycled glass fiber and stirring, and repeating the alternating feeding in this manner until all of them are added.
[0019] By adopting the above technical solution, since wood fibers are short and dispersed, while glass fibers have a certain aspect ratio, the batch-alternating addition can maintain the macroscopic shear viscosity stability of the material group in the reactor, reduce the phenomenon of instantaneous large-scale aggregation of the same type of fiber to form dry powder agglomeration, and help to achieve three-dimensional isotropic dispersion of the two types of cellulose in the resin paste.
[0020] Preferably, the step of injecting polymeric diphenylmethane diisocyanate into the mixture and then vacuum stirring, followed by discharging from the reactor, includes: rapidly injecting polymeric diphenylmethane diisocyanate into the mixture, turning on the reactor vacuum system to control the vacuum degree between -0.08MPa and -0.1MPa, vacuum stirring at low speed to remove air trapped during the mixing process, and then immediately discharging the material from the reactor.
[0021] By adopting the above technical solution, the injection of polymerized diphenylmethane diisocyanate at the end of the feeding process is mainly to shorten its residence time in the heating kettle and avoid early prepolymerization. Combined with low-speed stirring under negative pressure, the internal pressure difference forces the microbubbles introduced when the powder and fiber are mixed to overflow from the system, thereby reducing the porosity of the finished board.
[0022] Preferably, the step of placing the mixture discharged from the reactor in a closed environment for static curing until the material system presents a semi-solid plastic form includes: transferring the mixture discharged from the reactor to a closed storage box covered with PET film, and placing it in a constant temperature workshop at 25°C to 27°C for static curing for 24 to 36 hours; wherein, during the static curing process, polymeric diphenylmethane diisocyanate is used to react with the component containing free hydroxyl groups at room temperature to increase the viscosity of the system until the apparent viscosity of the material system increases, the surface loses its stickiness, and the whole system presents a semi-solid plastic form.
[0023] By adopting the above technical solution, the sealed environment and the coating operation isolate the ambient humidity and block the side reaction of isocyanate groups reacting with water to generate carbon dioxide gas. This maintains the single direction of the urethane esterification reaction and also improves the compactness of the material body.
[0024] Preferably, the steps of transferring the cured premix into the mold cavity, closing the mold, applying molding pressure, and heating and hot-pressing curing include: cutting the cured premix into pieces, weighing and spreading them evenly in the metal mold cavity, transferring the mold into a flat vulcanizing machine, closing the mold, applying a molding pressure of 8.8 MPa to 9.2 MPa, heating to 119°C to 121°C, and holding at temperature and pressure for 20 min to 25 min; wherein, during the heating and hot-pressing curing process, dicyandiamide and 2-methylimidazole are used to trigger the ring-opening addition reaction of bisphenol A epoxy resin at high temperature to construct the final cured crosslinking network.
[0025] By adopting the above technical solution, the set temperature range is matched with the activation temperature of dicyandiamide, which can promote the rapid gelation of the resin system. At the same time, the pressure of 8.8MPa to 9.2MPa forces the semi-solid premix to flow and fill the mold cavity, extruding the gap of the cured and cut blocks, so that the lap joint of wood fiber and glass fiber is more tightly bonded.
[0026] Preferably, the steps of maintaining molding pressure and performing step-by-step cooling, followed by opening the mold and ejecting the sheet material after cooling, and allowing it to cool and solidify naturally include: maintaining molding pressure after the curing stage, connecting the mold water cooling system for step-by-step slow cooling, opening the mold and ejecting the sheet material when the core temperature of the mold drops to 50°C to 60°C, and allowing the sheet material to cool naturally for 12 hours to room temperature for solidification.
[0027] By adopting the above technical solution, since the mold opening temperature of 50℃ to 60℃ is lower than the glass transition temperature of the bisphenol A type epoxy resin system after curing, the resin chain segments have been frozen at this temperature and can better withstand the shear stress generated by the demolding pin, thereby reducing the probability of board warping and deformation caused by demolding under high temperature and high elasticity.
[0028] Preferably, the wood fiber is physically crushed pine powder with a moisture content of no more than 0.5%; the polyvinyl butyral resin powder is a component containing free hydroxyl groups.
[0029] By adopting the above technical solution, the moisture content of wood fiber is strictly controlled, which aims to eliminate the interference of moisture in subsequent chemical reactions. As a long-chain polymer, polyvinyl butyral has hydroxyl groups on its molecular chain that not only participate in the construction of polyurethane network during the curing stage, but also play the role of toughening phase in the final cured system, thus appropriately reducing the brittleness of epoxy resin.
[0030] This application provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic composite flame-retardant boards. It has the following beneficial effects: 1. This application introduces a polyurethane prepolymer network in the epoxy resin matrix by introducing a polymerization of diphenylmethane diisocyanate to react with free hydroxyl groups in the system at room temperature. This mechanism enables the liquid mixed resin paste at the time of exiting the reactor to transform into a semi-solid plastic form with a non-sticky surface during the curing stage. This overcomes the problem of difficult viscosity control caused by high filling of wood fiber and glass fiber in conventional processes, and gives the material the processing properties of easy cutting, weighing and pressurizing for molding, thus improving the homogeneous molding effect of the multiphase mixed system in the mold.
[0031] 2. This application modifies the surface of recycled glass fibers from waste wind turbine blades by amylation. During the high-temperature hot-pressing curing stage, the active amino groups on the fiber surface undergo a ring-opening addition reaction with the ends of bisphenol A type epoxy resin. This chemical mechanism establishes covalent bonds between the inorganic glass fibers and the organic resin matrix, which compensates for the microscopic interface defects caused by conventional physical blending, improves the interfacial bonding force between the resin matrix and the reinforcing fibers, and realizes the material recycling of solid waste from wind turbine blades while ensuring the overall mechanical strength of the board.
[0032] 3. This application utilizes the latent curing properties of dicyandiamide at high temperatures to initiate the polymerization of epoxy groups, and maintains the molding pressure for a stepwise slow cooling process after curing. This pressure-cooling process allows the polymer chain segments to relax and rearrange before cooling and depressurization, absorbing and compensating for the volume shrinkage deformation energy caused by the high cross-linking density of epoxy resin, reducing the residual thermal stress generated inside the board due to temperature gradient and curing shrinkage, and reducing the risk of microcracks and warping deformation in the molded product. Attached Figure Description
[0033] Figure 1 This is a graph showing the change in apparent viscosity over time during the aging process of this application. Figure 2 Infrared spectra at different stages of this application; Figure 3 This is a thermogravimetric analysis weight loss curve for this application; Figure 4 This is a hot weight analysis curve of micro-business data in this application; Figure 5 This is a graph showing the bending strength versus tensile strength of this application; Figure 6 This is a graph showing the flexural modulus versus notched impact strength of this application. Figure 7 This is the dynamic thermomechanical analysis spectrum of this application; Figure 8 This is a scatter plot showing the macroscopic dimensional stability of this application. Detailed Implementation
[0034] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0035] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0036] The bisphenol A type epoxy resin selected is type E44, CAS number 25068-38-6, whose chemical name is a polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide.
[0037] The polyvinyl butyral resin powder is selected with a free hydroxyl mass fraction of 18% to 21%, and the CAS number is 63148-65-2.
[0038] Polymeric diphenylmethane diisocyanate is a liquid product with a chemical structure of a mixture of homologues of polymethylene polyphenyl polyisocyanate. The CAS number of polymethylene polyphenyl polyisocyanate is 9016-87-9, the average isocyanate functionality is 2.6 to 2.7, and the mass fraction of intramolecular free isocyanate (-NCO) is 30% to 32%.
[0039] The dicyandiamide used is a micron-grade product with CAS number 461-58-5 and an average solid particle size (D50) of no more than 20 μm.
[0040] The recycled glass fiber from waste wind turbine blades is derived from retired wind turbine blades. Its base material consists of alkali-free glass fiber and aged bisphenol A type epoxy resin cured on the surface, which is collected after mechanical coarse crushing and screening.
[0041] The wood fiber is made from pine wood powder prepared by physical crushing of pine wood material, which is then passed through a 200-mesh standard sieve and dried at 105℃ before use until the moisture content is no more than 0.5%.
[0042] 2-Methylimidazole was selected from commercially available industrial-grade products, with CAS number 693-98-1.
[0043] The aluminum hydroxide used is a micron-sized product with CAS number 21645-51-2 and an average particle size (D50) of 1 to 3 μm.
[0044] Montmorillonite is made from sodium-based natural layered silicate mineral powder, CAS number 1318-93-0, with an interlayer spacing of 1.2 to 1.5 nm.
[0045] Zinc stearate is selected from commercially available industrial-grade products, with CAS number 557-05-1.
[0046] 3-Aminopropyltriethoxysilane was selected from commercially available industrial grade products, CAS number 919-30-2. In this application, all units of measurement for materials and solvents are uniformly referred to as parts by weight.
[0047] Preparation Example 1: This preparation example provides a method for preparing surface-aminated recycled glass fibers from waste wind turbine blades: The waste wind turbine blades are mechanically crushed in multiple stages by a crusher, and then screened to remove waste glass fiber coarse material with a length of 4mm. The above coarse material was immersed in a 5% sodium hydroxide aqueous solution at a solid-liquid mass-volume ratio of 1g:10mL and ultrasonically treated at 60℃ for 30min to swell and peel off some of the aged resin residue and impurities attached to the surface; then it was washed with deionized water until neutral and dried in an 80℃ forced-air drying oven for later use. A 2% (w / w) ethanol-water mixed solution of 3-aminopropyltriethoxysilane was prepared, wherein the volume ratio of anhydrous ethanol to deionized water was 9:1. The pH was adjusted to 5.0 with glacial acetic acid and subjected to hydrolysis pretreatment for 15 min. The dried recycled glass fiber was added to the hydrolysate at a solid-liquid mass-volume ratio of 1 g: 15 mL and impregnated at high speed at room temperature for 45 min. After filtration, the glass fiber was cross-linked and dried in a vacuum oven at 110℃ for 2 h to obtain modified recycled glass fiber with a surface rich in active amino groups.
[0048] Preparation Example 2: This preparation example provides a method for preparing surface-aminated recycled glass fibers from waste wind turbine blades: The waste wind turbine blades are mechanically crushed in multiple stages by a crusher, and then screened to remove waste glass fiber coarse material with a length of 3mm. The above coarse material was immersed in a 3% sodium hydroxide aqueous solution at a solid-liquid mass-volume ratio of 1g:10mL and ultrasonically treated at 50℃ for 20min to swell and peel off some of the aged resin residue and impurities attached to the surface. The recycled glass fibers were then washed with deionized water until neutral and dried in an 80°C forced-air drying oven for later use. A 1% (w / w) ethanol-water mixed solution of 3-aminopropyltriethoxysilane was prepared, with an anhydrous ethanol to deionized water volume ratio of 9:1. The pH was adjusted to 4.5 with glacial acetic acid and subjected to hydrolysis pretreatment for 10 min. The dried recycled glass fibers were added to the hydrolysate at a solid-liquid mass-volume ratio of 1 g:15 mL and impregnated at high speed at room temperature for 30 min. After filtration, the fibers were placed in a vacuum oven at 100°C for cross-linking and drying for 1.5 h to obtain modified recycled glass fibers with a surface rich in active amino groups.
[0049] Preparation Example 3: This preparation example provides a method for preparing surface-aminated recycled glass fibers from waste wind turbine blades: The waste wind turbine blades are mechanically crushed in multiple stages by a crusher, and then screened to remove waste glass fiber coarse material with a length of 5mm. The above coarse material was immersed in a 7% sodium hydroxide aqueous solution at a solid-liquid mass-volume ratio of 1g:10mL and ultrasonically treated at 70℃ for 40min to swell and peel off some of the aged resin residue and impurities attached to the surface. The recycled glass fibers were then washed with deionized water until neutral and dried in an 80°C forced-air drying oven for later use. A 3% (w / w) ethanol-water mixed solution of 3-aminopropyltriethoxysilane was prepared, with an anhydrous ethanol to deionized water volume ratio of 9:1. The pH was adjusted to 5.5 with glacial acetic acid and subjected to hydrolysis pretreatment for 20 min. The dried recycled glass fibers were added to the hydrolysate at a solid-liquid mass-volume ratio of 1 g:15 mL and impregnated at high speed at room temperature for 60 min. After filtration, the fibers were placed in a vacuum oven at 120°C for cross-linking and drying for 2.5 h to obtain modified recycled glass fibers with a surface rich in active amino groups.
[0050] Example 1: This embodiment provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic composite flame-retardant boards, including the following steps: In a reactor equipped with a high-speed dispersion speed-regulating motor and a vacuum system, 30 parts of bisphenol A type epoxy resin were added and heated to 55°C to reduce the initial viscosity of the resin. Then, 4.5 parts of polyvinyl butyral resin powder were added in batches and sheared and stirred at 900 rpm for 25 minutes to fully dissolve the polyvinyl butyral resin powder and uniformly disperse it in the epoxy matrix to form a homogeneous toughening resin liquid. The solution was then cooled to 28°C.
[0051] Keep the reactor temperature at 28℃, and slowly add 3 parts of dicyandiamide, 0.35 parts of 2-methylimidazole and 0.75 parts of zinc stearate at 500 rpm. Stir until homogeneous. Then slowly sieve the premixed composite flame retardant filler, which is composed of 12 parts of aluminum hydroxide and 3 parts of montmorillonite, into the system. Increase the speed to 1000 rpm and stir for 15 minutes until a homogeneous resin paste is formed.
[0052] Reduce the stirring speed to 350 rpm, and add 37 parts of wood fiber with a moisture content of no more than 0.5% and 23 parts of surface-aminated waste wind turbine blade recycled glass fiber A using a batch alternating feeding method: first add one-third of the wood fiber and stir for 3 minutes, then add one-third of the surface-aminated waste wind turbine blade recycled glass fiber A and stir for 3 minutes. Repeat this cycle three times until all the powder and fiber are mixed in, and control the total mixing time to 18 minutes.
[0053] Five minutes before discharge, 3.5 parts of polymerized diphenylmethane diisocyanate were rapidly injected into the above mixture. The vacuum system of the reactor was turned on to make the vacuum degree -0.09MPa. The mixture was stirred under vacuum at a low speed of 200rpm for 4 minutes to remove the air trapped in the mixing process. The material was then discharged from the reactor immediately.
[0054] Transfer the mixture to a sealed storage box covered with PET film and place it in a constant temperature workshop at 25°C for 30 hours to mature. When the apparent viscosity of the system increases, the surface of the material loses its stickiness, and the whole thing presents a semi-solid plastic state, the maturation and thickening is complete.
[0055] Cut the matured premix into pieces and weigh them. Spread them evenly in the cavity of a stainless steel metal mold. Move the mold into a flat vulcanizing machine. After closing the mold, apply a molding pressure of 9.0 MPa, heat to 120°C, and hold for 22 minutes.
[0056] After the curing stage, maintain a molding pressure of 9.0 MPa, connect the mold water cooling system to slowly cool down in stages, and open the mold to eject the board when the core temperature of the mold drops to 55℃. Let the board cool naturally for 12 hours to room temperature to set, and you will get the recycled glass fiber reinforced epoxy wood-plastic flame retardant board.
[0057] Example 2: This embodiment provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic composite flame-retardant boards, including the following steps: In a reactor equipped with a high-speed dispersion speed-regulating motor and a vacuum system, 25 parts of bisphenol A type epoxy resin were added and heated to 60°C to reduce the initial viscosity of the resin. Then, 3 parts of polyvinyl butyral resin powder were added in batches and sheared and stirred at 1000 rpm for 30 minutes to fully dissolve the polyvinyl butyral resin powder and uniformly disperse it in the epoxy matrix to form a homogeneous toughening resin liquid. The solution was then cooled to 25°C.
[0058] Keep the reactor temperature at 25°C. At 500 rpm, slowly add 2 parts dicyandiamide, 0.2 parts 2-methylimidazole and 1 part zinc stearate in sequence and stir evenly. Then, slowly sieve the premixed composite flame retardant filler, which is composed of 16 parts aluminum hydroxide and 4 parts montmorillonite, into the system and increase the speed to 1000 rpm and stir for 15 minutes until a homogeneous resin paste is formed.
[0059] Reduce the stirring speed to 400 rpm, and add 45 parts of wood fiber with a moisture content of no more than 0.5% and 30 parts of surface-aminated waste wind turbine blade recycled glass fiber B using a batch alternating feeding method: first add one-third of the wood fiber and stir for 3 minutes, then add one-third of the surface-aminated waste wind turbine blade recycled glass fiber B and stir for 3 minutes. Repeat this cycle three times until all the powder and fiber are mixed in, and control the total mixing time to 20 minutes.
[0060] Five minutes before discharge, two parts of polymerized diphenylmethane diisocyanate were rapidly injected into the above mixture. The vacuum system of the reactor was turned on to make the vacuum degree -0.08MPa. The mixture was stirred under vacuum at a low speed of 200rpm for 5 minutes to remove the air trapped in the mixing process. The material was then discharged from the reactor immediately.
[0061] Transfer the mixture to a sealed storage box covered with PET film and place it in a constant temperature workshop at 25°C for 24 hours to mature. When the apparent viscosity of the system increases, the surface of the material loses its stickiness, and the whole thing presents a semi-solid plastic state, the maturation and thickening is complete.
[0062] Cut the matured premix into pieces and weigh them. Spread them evenly in the cavity of a stainless steel metal mold. Move the mold into a flat vulcanizing machine. After closing the mold, apply a molding pressure of 8.8 MPa, heat to 119°C, and keep warm and pressurized for 20 minutes.
[0063] After the curing stage, maintain a molding pressure of 8.8 MPa, connect the mold water cooling system to slowly cool down in stages, and open the mold to eject the board when the core temperature of the mold drops to 50°C. Let the board cool naturally for 12 hours to room temperature to set, and you will get the recycled glass fiber reinforced epoxy wood-plastic flame retardant board.
[0064] Example 3: This embodiment provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic composite flame-retardant boards, including the following steps: In a reactor equipped with a high-speed dispersion speed-regulating motor and a vacuum system, 35 parts of bisphenol A type epoxy resin were added and heated to 50°C to reduce the initial viscosity of the resin. Then, 6 parts of polyvinyl butyral resin powder were added in batches and sheared and stirred at 800 rpm for 20 minutes to fully dissolve the polyvinyl butyral resin powder and uniformly disperse it in the epoxy matrix to form a homogeneous toughening resin liquid. The solution was then cooled to 30°C.
[0065] Keep the reactor temperature at 30℃, and slowly add 4 parts of dicyandiamide, 0.5 parts of 2-methylimidazole and 0.5 parts of zinc stearate at 500 rpm. Stir until homogeneous. Then slowly sieve the premixed composite flame retardant filler, which is composed of 8 parts of aluminum hydroxide and 2 parts of montmorillonite, into the system. Increase the speed to 1000 rpm and stir for 15 minutes until a homogeneous resin paste is formed.
[0066] Reduce the stirring speed to 300 rpm, and add 30 parts of wood fiber with a moisture content of no more than 0.5% and 15 parts of surface-aminated waste wind turbine blade recycled glass fiber C using a batch alternating feeding method: first add one-third of the wood fiber and stir for 3 minutes, then add one-third of the surface-aminated waste wind turbine blade recycled glass fiber C and stir for 3 minutes. Repeat this cycle three times until all the powder and fiber are mixed in, and control the total mixing time to 15 minutes.
[0067] Five minutes before discharge, five parts of polymerized diphenylmethane diisocyanate were rapidly injected into the above mixture. The vacuum system of the reactor was turned on to make the vacuum degree -0.1MPa. The mixture was stirred under vacuum at a low speed of 200rpm for 3 minutes to remove the air trapped in the mixing process. The material was then discharged from the reactor immediately.
[0068] Transfer the mixture to a sealed storage box covered with PET film and place it in a constant temperature workshop at 27°C for 36 hours to mature. When the apparent viscosity of the system increases, the surface of the material loses its stickiness, and the whole thing presents a semi-solid plastic state, the maturation and thickening is complete.
[0069] Cut the matured premix into pieces and weigh them. Spread them evenly in the cavity of a stainless steel metal mold. Move the mold into a flat vulcanizing machine. After closing the mold, apply a molding pressure of 9.2 MPa, heat to 121°C, and hold for 25 minutes.
[0070] After the curing stage, maintain a molding pressure of 9.2 MPa, connect the mold water cooling system to slowly cool down in stages, and open the mold to eject the board when the core temperature of the mold drops to 60°C. Let the board cool naturally for 12 hours to room temperature to set, and you will get the recycled glass fiber reinforced epoxy wood-plastic flame retardant board.
[0071] Example 4: This embodiment provides a method for preparing recycled glass fiber reinforced epoxy wood-plastic composite flame-retardant boards, including the following steps: In a reactor equipped with a high-speed dispersion speed-regulating motor and a vacuum system, 30 parts of bisphenol A type epoxy resin were added and heated to 60°C to reduce the initial viscosity of the resin. Then, 4.5 parts of polyvinyl butyral resin powder were added in batches and sheared and stirred at 1000 rpm for 30 minutes to fully dissolve the polyvinyl butyral resin powder and uniformly disperse it in the epoxy matrix to form a homogeneous toughening resin liquid. The solution was then cooled to 30°C.
[0072] Keep the reactor temperature at 30℃, and slowly add 3 parts of dicyandiamide, 0.35 parts of 2-methylimidazole and 0.75 parts of zinc stearate at 500 rpm. Stir until homogeneous. Then slowly sieve the premixed composite flame retardant filler, which is composed of 12 parts of aluminum hydroxide and 3 parts of montmorillonite, into the system. Increase the speed to 1000 rpm and stir for 15 minutes until a homogeneous resin paste is formed.
[0073] Reduce the stirring speed to 400 rpm and add 37 parts of wood fiber with a moisture content of no more than 0.5% and 23 parts of surface-aminated waste wind turbine blade recycled glass fiber A using a batch alternating feeding method: first add one-third of the wood fiber and stir for 3 minutes, then add one-third of the surface-aminated waste wind turbine blade recycled glass fiber A and stir for 3 minutes. Repeat this cycle three times until all the powder and fiber are mixed in. The total mixing time is controlled within 20 minutes.
[0074] Five minutes before discharge, 3.5 parts of polymerized diphenylmethane diisocyanate were rapidly injected into the above mixture. The vacuum system of the reactor was turned on to make the vacuum degree -0.1MPa. The mixture was stirred under vacuum at a low speed of 200rpm for 5 minutes to remove the air trapped in the mixing process. The material was then discharged from the reactor immediately.
[0075] Transfer the mixture to a sealed storage box covered with PET film and place it in a constant temperature workshop at 25°C for 36 hours to mature. When the apparent viscosity of the system increases, the surface of the material loses its stickiness, and the whole thing presents a semi-solid plastic state, the maturation and thickening is complete.
[0076] Cut the matured premix into pieces and weigh them. Spread them evenly in the cavity of a stainless steel metal mold. Move the mold into a flat vulcanizing machine. After closing the mold, apply a molding pressure of 9.2 MPa, heat to 121°C, and hold for 25 minutes.
[0077] After the curing stage, maintain a molding pressure of 9.2 MPa, connect the mold water cooling system to slowly cool down in stages, and open the mold to eject the board when the core temperature of the mold drops to 60°C. Let the board cool naturally for 12 hours to room temperature to set, and you will get the recycled glass fiber reinforced epoxy wood-plastic flame retardant board.
[0078] Comparative Example 1: Compared with Example 1, the difference is that the polymeric diphenylmethane diisocyanate is replaced with an equal amount of magnesium oxide, and all other aspects are the same.
[0079] Comparative Example 2: Compared with Example 1, the difference is that the polyvinyl butyral resin powder is replaced with an equal amount of polyvinyl chloride powder, and all other aspects are the same.
[0080] Comparative Example 3: Compared with Example 1, the difference is that the surface-aminated waste wind turbine blade recycled glass fiber A is replaced with an equal amount of unmodified waste glass fiber coarse material, that is, it is only mechanically crushed and screened, without alkali washing and coupling modification, and the rest are the same.
[0081] Comparative Example 4: Compared with Example 1, the difference is that the composite flame retardant filler is replaced with an equal amount of single aluminum hydroxide flame retardant, that is, montmorillonite is removed, and 15 parts of composite flame retardant filler are replaced with 15 parts of pure aluminum hydroxide, while the rest are the same.
[0082] Comparative Example 5: Compared with Example 1, the difference is that after the curing stage, the mold water cooling system is not connected for step cooling. Instead, the mold is opened and the plate is ejected directly at 120°C and then rapidly cooled at room temperature. All other aspects are the same.
[0083] Test Example 1: Take 200g of the initial liquid mixture after discharge from the reactor of Example 1 and Comparative Example 1, and place them in a constant temperature and humidity test chamber set to 25°C for standing.
[0084] Continuous dynamic viscosity monitoring was performed using a parallel plate rotational rheometer. A parallel plate test fixture with a diameter of 25 mm was selected, the fixture gap was set to 1.0 mm, the test temperature was controlled at 25℃, and the shear rate was set to 1 s. -1 The time from when the sample is placed in the constant temperature chamber is 0 hours. Samples are taken and tested every 6 hours, and the total monitoring time is 36 hours. The changes in the apparent viscosity of the system are recorded.
[0085] Take 2g of the semi-solid premix from Example 1 after standing and maturing for 30 hours, and after performing a curing and molding step of hot pressing at 120°C for 22 minutes, take 2g of the resulting board sample.
[0086] The samples obtained in the above two stages were placed in liquid nitrogen for low-temperature cryogenic embrittlement, pulverized into micron-sized powder using a vibratory ball mill, and the powder that passed through a 400-mesh standard sieve was collected. The powder was then mixed and ground with spectral-grade potassium bromide powder at a mass ratio of 1:100, and then prepared into transparent test sheets by applying a pressure of 10 MPa on an infrared tablet press.
[0087] The pressed potassium bromide sheet was placed in the sample chamber of the Fourier transform infrared spectrometer, and the scanning wavenumber range was set to 400 to 4000 cm⁻¹. -1 The number of scans was 32, and the resolution was 4cm. -1 The collected spectra were baseline calibrated at 1510 cm⁻¹. -1 The absorption peak of the benzene ring skeleton vibration at 2270 cm⁻¹ was used as an internal standard to extract the -NCO group in the system. -1 (place) and epoxy group (914cm) -1 The characteristic peak absorbance of (location) is calculated and the relative intensity retention is compared.
[0088] Table 1: Data on the change of apparent viscosity of the system during the maturation stage
[0089] Table 2: Ratio of relative absorbance of key characteristic peaks at different process stages in Example 1
[0090] According to Table 1 and Figure 1 and Figure 2 It can be seen that, in Comparative Example 1, using traditional magnesium oxide as a thickener, the apparent viscosity decreased only from 11.82 × 10⁻⁶ during the 36-hour test period. 3 Pa·s fluctuated slightly to 13.92 × 10 3 Pa·s indicates that inorganic alkaline earth metal oxides cannot interact with the epoxy resin backbone lacking free carboxyl groups, and the system failed to achieve the transition to the B-stage semi-solid state. In Example 1, after using polymerized diphenylmethane diisocyanate, the apparent viscosity of the system increased exponentially over time, reaching 212.87 × 10⁻⁶ Pa·s after 30 hours. 3 Pa·s, the physical form of the material changes to a cheese-like state suitable for molding operation, verifying the feasibility of the room temperature prepolymerization thickening mechanism; the relative absorbance ratio of -NCO groups calculated by theory for the initial liquid sample after exiting the reactor is 0.88, and the relative absorbance ratio of epoxy groups is 1.12.
[0091] According to Table 2 and Figure 1 and Figure 2 It can be seen that, after 30 hours of room temperature standing and aging, the 2270 cm⁻¹, representing isocyanate, in Example 1 -1The relative absorbance of the characteristic peak decreased to 0.02, indicating that the added isocyanate had been largely consumed and had undergone chain extension reactions with the free hydroxyl groups in the wood fibers and polyvinyl butyral resin; simultaneously, the 914 cm⁻¹ peak, representing the epoxy groups... -1 The characteristic peak absorbance ratio remained at 1.09, with no significant decrease compared to the theoretical initial value, proving that no cross-linking of epoxy groups was initiated during the room temperature curing stage. After the hot-pressing stage at 120℃, the absorbance reached 914 cm⁻¹. -1 The relative absorbance at this temperature drops sharply to 0.05, indicating that the latent curing agent is effectively activated at this temperature, driving the high-density ring-opening curing of the matrix resin. This test result confirms the technical logic of the two cross-linking networks of polyurethane prepolymerization and epoxy main curing being constructed in steps without interference at the microscopic molecular scale.
[0092] Test Example 2: Take 50g of each of the solidified and naturally cooled plates from Example 1 and Comparative Example 1, grind them into powder using a micro pulverizer, and collect the powder samples that pass through a 200-mesh standard sieve as the test objects for thermogravimetric analysis.
[0093] Weigh 7.2 mg of the powder sample from Example 1 and 7.5 mg of the powder sample from Comparative Example 4 prepared above, and place them in alumina crucibles respectively. In a thermogravimetric analyzer, high-purity nitrogen is set as the purge gas, the gas flow rate is controlled at 50 mL / min, the test program is set to the initial temperature of 30℃, and the temperature is heated to 800℃ at a heating rate of 10℃ / min. The characteristic data of sample mass change with temperature are continuously recorded, and the 5% thermogravimetric temperature, the temperature corresponding to the maximum thermogravimetric rate, and the char residue at 800℃ are extracted.
[0094] According to ASTM D2863, the plates of Example 1 and Comparative Example 4 were mechanically cut into strips of 120mm × 10mm × 4mm, with 10 strips prepared for each group. The samples were vertically fixed in the combustion chamber of the limiting oxygen index instrument. By adjusting the mixed flow rate of oxygen and nitrogen, the top of the sample was ignited, and the minimum oxygen volume fraction required to maintain stable combustion of the sample for 3 minutes or to achieve a combustion length of 50mm was tested.
[0095] According to ASTM D3801 standard, the plates of Example 1 and Comparative Example 4 were mechanically cut into 125mm × 13mm × 4mm vertical burning standard test specimens, with 5 specimens prepared for each group. After conditioning for 48 hours at an ambient temperature of 23℃ and a relative humidity of 50%, the specimens were vertically clamped, and a standard methane Bunsen burner flame was used to ignite the bottom of the specimen for 10 seconds. After the flame was removed, the flaming burning time of the specimen was recorded. After the flame was extinguished, it was ignited again for 10 seconds, and the second flaming burning time and smoldering time were recorded. At the same time, degreased cotton was placed 300mm below the specimen, and it was observed whether there were any micro-droplets that ignited the degreased cotton during the combustion process, in order to evaluate the UL-94 flame retardancy rating of the specimen.
[0096] Table 3: Comparison of Key Thermogravimetric Analysis Data between Example 1 and Comparative Example 4
[0097] Table 4: Comparison of Macroscopic Combustion Performance Test Data between Example 1 and Comparative Example 4
[0098] According to Tables 3 and 4, and Figure 3 and Figure 4 It can be seen that Comparative Example 4 uses aluminum hydroxide as a single flame retardant. During the heating stage, aluminum hydroxide undergoes a dehydration endothermic reaction, and the released water vapor plays a role in diluting combustible gases and reducing surface temperature. However, the final decomposition product is loose and porous alumina, which cannot build a barrier layer with sufficient mechanical strength on the surface of the polymer matrix. This leads to continuous thermal degradation inside the matrix, and the char rate at 800℃ is only 19.5%. This loose residue structure cannot support the molten polymer network in the high-temperature vertical combustion test, resulting in dripping at the edge of the Comparative Example 5 sample. The limiting oxygen index remains at 26.7%, and the flame retardant rating fails to reach V-0.
[0099] In Example 1, after introducing a composite flame-retardant filler composed of aluminum hydroxide and montmorillonite, the 5% thermogravimetric temperature of the system increased from 298.1℃ to 312.4℃, and the peak value of the maximum thermal degradation rate shifted to the high-temperature region by 25.5℃. Montmorillonite is a two-dimensional layered silicate that exhibits an interlayer exfoliation dispersion state in the dual crosslinking network of polyurethane and epoxy resin. When the material is thermally degraded, the montmorillonite sheets exert a physical labyrinth barrier effect, restricting the thermal movement of polymer molecular chain segments and the outward diffusion of volatile small molecule gases. With the endothermic dehydration of aluminum hydroxide, montmorillonite will undergo surface migration and crosslink with the products of high-temperature carbonization of the matrix resin, forming a dense and continuous silicate carbon composite protective layer in situ on the material surface.
[0100] The formation of the silicate-carbon composite protective layer cuts off the exchange path between the internal unreacted matrix and the external oxygen and heat, increasing the char rate at 800℃ to 32.8%. The hard silicate-carbon layer inhibits the high-temperature softening and collapse of the matrix, eliminates melting and dripping, and raises the limiting oxygen index to 31.4%. The test sample successfully passed the UL-94V-0 flame retardant standard. The above results confirm that there is a synergistic effect of flame retardant char formation between inorganic metal hydrates and layered silicates in the polymer network of this application.
[0101] Test Example 3: The boards from Examples 1, 2, 3, 4 and Comparative Example 3 that were hot-pressed, cured and naturally cooled to room temperature were selected as test subjects.
[0102] CNC cutting equipment was used to cut and process each group of plates into specimens that meet the corresponding mechanical test standard dimensions. The cutting edges of the specimens were sanded with sandpaper to eliminate minor edge defects generated during the processing. Ten independent specimens were prepared for each mechanical performance test to obtain average effective data.
[0103] Tensile properties were tested on a microcomputer-controlled electronic universal testing machine. The initial clamping distance was set to 115 mm, and the tensile loading rate was kept constant at 5 mm per minute. The maximum tensile load at which the specimen fractured was recorded and the corresponding tensile strength was calculated.
[0104] Three-point bending performance tests were conducted on the same universal testing machine. The support span was set to 16 times the specimen thickness, and the central indenter loading rate was set to 2 mm per minute. The data on the central displacement and load change were continuously recorded, and the bending strength and bending modulus of the specimen were calculated.
[0105] A type A notch with a depth of 2 mm was machined on one side of the middle section of a specimen of specified size using a cantilever beam impact notch preparation machine. Then, an impact test was conducted on the back side of the notch using a pendulum with a nominal energy of 4 joules on a simply supported beam impact testing machine. The energy consumed by the pendulum to break the specimen was read, and the impact strength of the simply supported beam notch was calculated.
[0106] Table 5: Test data of macroscopic mechanical properties of Examples 1 to 4 and Comparative Example 3
[0107] According to Table 5 and Figure 5 and Figure 6 It can be seen that the bending strength of Examples 1 to 4 all remained above 89.6 MPa, the tensile strength was greater than 56.2 MPa, and the notched impact strength of the simply supported beam was not lower than 11.4 kJ / m. 2 This demonstrates that within the component ratio range specified in this application, regardless of whether it is a resin-poor state with a high skeleton filler ratio or a resin-rich state with a high resin content, and under the process boundary conditions of adjusting the curing time and molding pressure, the composite system of matrix resin and recycled glass fiber can maintain stable structural integrity and mechanical transmission path. In Comparative Example 3, with other components and process conditions consistent with Example 1, only the surface-aminated recycled glass fiber from waste wind turbine blades was replaced with unmodified recycled glass fiber, resulting in a decrease in tensile strength to 33.7 MPa and a notched impact strength of simply supported beams to 5.6 kJ / m. 2 .
[0108] Unmodified waste glass fibers have a large amount of aged resin residue on their surface and lack chemically reactive functional groups. They cannot participate in the construction of the polymer network during the room temperature isocyanate chain extension and thickening stage and the high temperature epoxy ring-opening curing stage. This results in only weak physical contact between the glass fiber and the matrix resin, with low interfacial adhesion. When subjected to external loads, the stress inside the matrix cannot be effectively transferred to the glass fiber, which serves as the skeleton reinforcement material, through the interface, leading to stress concentration and slippage at the interface.
[0109] The surface-aminated glass fibers have amino groups on their surface that react with isocyanates in the polymerized diphenylmethane diisocyanate at room temperature to form urea bonds. At high temperature, these urea bonds act as amine curing agents and directly participate in the ring-opening addition reaction of the epoxy resin, establishing a two-way chemical covalent bridge between the inorganic fiber and the organic resin matrix. This multiphase interface locking mechanism binds the recycled glass fibers to the interpenetrating polymer network, hindering crack propagation within the matrix and resulting in high macroscopic mechanical properties in the embodiments.
[0110] Test Example 4: Rectangular strips with dimensions of 50mm × 10mm × 3mm were cut from the plates prepared in Examples 1, 2, and 5 and left to stand for 48 hours using a water jet cutting device for dynamic thermomechanical property analysis. The edges of the strips were polished to remove cutting burrs and ensure that the sample surface was flat and free of defects.
[0111] The spline was clamped in the single cantilever beam fixture of the dynamic thermomechanical analyzer. The dynamic strain mode was set, the vibration frequency was set to 1 Hz, the amplitude was 20 μm, the test temperature range was set to 30℃ to 200℃, and the programmed heating rate was controlled at 3℃ / min. During the test, the data of the storage modulus and loss tangent as a function of temperature were collected simultaneously. The temperature corresponding to the main peak of the loss tangent was recorded as the glass transition temperature of the system, and the half-width at half-maximum (WHM) value of the peak width was extracted.
[0112] A 300mm×300mm integral molded sheet was selected as the macroscopic deformation test sample. The sheet was placed on the worktable of a high-precision coordinate measuring machine. The geometric center of the sheet was used as the reference zero plane. The maximum normal displacement of the four corner points of the sheet from the reference plane was measured. The warpage was calculated as a percentage of the maximum displacement divided by the diagonal length of the sheet.
[0113] The initial density of the premix after curing and the final density of the molded board after curing and cooling were determined using the water displacement density method. The volume shrinkage rate of each sample was calculated based on the density changes before and after the test, and the test values were recorded.
[0114] Table 6: Data on Key Dynamic Thermomechanical Parameters and Dimensional Stability Measurement
[0115] According to Table 6 and Figure 7 and Figure 8 It can be seen that, in Comparative Example 2, when polyvinyl chloride powder with traditional low shrinkage agent was used to replace polyvinyl butyral resin, two distinct independent peaks appeared in the loss tangent curve of dynamic thermomechanical analysis: 129.5℃ and 92.1℃. This indicates that the polarity of the polyvinyl chloride molecular chain and the epoxy resin is mismatched, resulting in severe macroscopic phase separation during the curing and crosslinking process. Since polyvinyl chloride cannot participate in the isocyanate chain extension reaction and fails to anchor in the crosslinking network, the frictional internal friction capacity between the macromolecular chain segments inside the system decreases, and the full width at half maximum (FWHM) of the main peak is only 21.3℃. When the epoxy resin undergoes severe crosslinking shrinkage at a high temperature of 120℃, the disjointed free phase cannot disperse in situ and compensate for the huge internal stress generated by the volume deformation, resulting in a volume shrinkage rate of 1.45% for the molded board. The release of crosslinking internal stress directly leads to a warpage of up to 2.58% for the board, and microscopic delamination is also observed at the edge of the board.
[0116] In Example 1, polyvinyl butyral resin was introduced into the formulation. The loss tangent curve showed a single and gentle broad peak shape, with a half-width at half-maximum of 47.6°C and a glass transition temperature of 134.2°C. This confirms that the free hydroxyl groups on the polyvinyl butyral resin segments have been incorporated into the polyurethane flexible network through chemical bonding, achieving microscopic compatibility in the epoxy matrix. During the high-temperature curing stage, the highly compatible and flexible polyvinyl butyral molecular segments play a role in stress dissipation and volume compensation, absorbing the shrinkage deformation energy brought about by the high-density cross-linking of epoxy resin, thereby reducing the volume shrinkage rate to 0.38%.
[0117] Comparative Example 5 abandoned the mold water-cooling stepped cooling step after the curing stage, and directly depressurized and opened the mold at high temperature and rapidly cooled at room temperature. Although its basic material formula was the same as that of Example 1, and the volume shrinkage rate was controlled by the formula to maintain at 0.45%, its warpage climbed to 1.96%. Due to the severe temperature gradient difference between the surface of the board and the core layer, the asynchronous thermal expansion and contraction caused by rapid cooling induced a large amount of residual thermal stress in the thickness direction of the material. Example 1 implemented a mold water-cooling system for stepped and slow cooling to ensure a uniform transition of temperature inside and outside the board and avoid the accumulation of residual thermal stress. The material smoothly crossed the glass transition zone under the constraint of the mold, and the warpage was extremely low when ejected, only 0.12%, maintaining long-term physical dimensional stability.
[0118] Although embodiments of this application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant boards, characterized in that, Includes the following steps: The viscosity of bisphenol A epoxy resin is reduced by heating, and polyvinyl butyral resin powder is added and sheared and stirred to form a homogeneous toughening resin liquid. Dicyandiamide, 2-methylimidazole and zinc stearate were added to the toughening resin solution in sequence and stirred evenly. The composite flame retardant filler was then sieved in and stirred to form a homogeneous resin paste. Wood fibers and surface-aminated modified waste wind turbine blade recycled glass fibers are added to the resin paste in batches and alternately, and then mixed to form a mixture. Polymerized diphenylmethane diisocyanate was injected into the mixture and stirred under vacuum, then discharged from the reactor; The mixture discharged from the reactor is placed in a closed environment to stand and mature until the material system presents a semi-solid plastic form. The matured premixed material is transferred into the mold cavity, the mold is closed, molding pressure is applied, and it is heated and hot-pressed to cure. Maintain molding pressure and perform step-by-step cooling. After cooling is complete, open the mold, eject the sheet, and allow it to cool and solidify naturally.
2. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The raw materials used to prepare the board comprise the following components in parts by weight: 25 to 35 parts of bisphenol A type epoxy resin; 3 to 6 parts of polyvinyl butyral resin powder; Dicyandiamide 2 to 4 parts; 0.2 to 0.5 parts of 2-methylimidazole; 0.5 to 1 part zinc stearate; 10 to 20 parts of composite flame-retardant filler; 30 to 45 parts of wood fiber; 15 to 30 parts of recycled glass fiber from waste wind turbine blades with surface amination modification; 2 to 5 parts of polymerized diphenylmethane diisocyanate.
3. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The surface-aminated recycled glass fiber from waste wind turbine blades is a coarse waste glass fiber material that retains the original fiber length, and its outer surface has an active amino layer generated by the hydrolysis and cross-linking of 3-aminopropyltriethoxysilane.
4. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The composite flame-retardant filler is composed of aluminum hydroxide and montmorillonite; and the weight ratio of aluminum hydroxide to montmorillonite is 4:
1.
5. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The step of adding wood fiber and surface-aminated modified waste wind turbine blade recycled glass fiber to the resin paste using a batch-alternating feeding method and mixing them to form a mixture includes: The total amount of wood fiber and the total amount of surface-aminated recycled glass fiber from waste wind turbine blades are divided into multiple equal parts. First, add one part of wood fiber and stir. Then, add one part of surface-aminated recycled glass fiber from waste wind turbine blades and stir. Repeat this process in an alternating manner until all the fibers are added.
6. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The step of injecting the polymerized diphenylmethane diisocyanate into the mixture and then vacuum stirring it, followed by discharging it from the reactor, includes: Polymerized diphenylmethane diisocyanate is rapidly injected into the mixture. The vacuum system of the reactor is turned on to control the vacuum level between -0.08MPa and -0.1MPa. The mixture is stirred at low speed to remove the air trapped in the mixing process, and then the material is immediately discharged from the reactor.
7. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The step of placing the mixture discharged from the reactor in a sealed environment for static maturation until the material system exhibits a semi-solid, plastic state includes: The mixture discharged from the reactor is transferred to a sealed storage box covered with PET film and placed in a constant temperature workshop at 25°C to 27°C for 24 to 36 hours to mature. During the maturation process, polymerized diphenylmethane diisocyanate is used to react with components containing free hydroxyl groups at room temperature to increase the viscosity of the system until the apparent viscosity of the material system increases, the surface loses its stickiness, and the whole system presents a semi-solid plastic form.
8. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The steps of transferring the cured premixed material into the mold cavity, closing the mold, applying molding pressure, and heating and hot-pressing for curing include: The cured premixed material is cut into blocks, weighed, and laid flat in the cavity of a metal mold. The mold is then moved into a flat vulcanizing machine. After the mold is closed, a molding pressure of 8.8 MPa to 9.2 MPa is applied, and the temperature is heated to 119°C to 121°C. The temperature and pressure are maintained for 20 to 25 minutes. During the hot-press curing process, dicyandiamide and 2-methylimidazole are used to trigger the ring-opening addition reaction of bisphenol A epoxy resin at high temperature to construct the final cured crosslinking network.
9. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The steps of maintaining molding pressure for stepped cooling, followed by mold opening, ejection of the sheet material, and natural cooling and solidification after cooling include: After the curing stage is completed, maintain the molding pressure, turn on the mold water cooling system to slowly cool down in stages, and open the mold to eject the board when the core temperature of the mold drops to 50℃ to 60℃. Let the board cool naturally for 12 hours to room temperature to set.
10. The method for preparing recycled glass fiber reinforced epoxy wood-plastic flame-retardant board according to claim 1, characterized in that, The wood fiber is physically pulverized pine powder with a moisture content of no more than 0.5%; the polyvinyl butyral resin powder is a component containing free hydroxyl groups.